Attendance barriers experienced by female health care workers voluntarily participating in a multi-component health promotion programme at the workplace - Pia Maria Ilvig; Thomas Viskum Gjelstrup Bredahl; Just Bendix Justesen; Dorrie Jones; Jonna Benner Lundgaard; Karen Søgaard; Jeanette Reffstrup Christensen (BMC, 2018)
Abstract Background Studies have shown that Workplace Health Promoting Programmes (WHPP) can facilitate healthier behaviour. Despite the benefits achieved from participating in a WHPP, a systematic review showed that only 10-50% of the employees participated and a challenge was lack of participation. Previous studies stress that understanding the barriers that prevent participants from attending WHPPs are important for designing highly effective interventions. To exploit the potential of a WHPP, it requires a deep insight into the attendance barriers experienced by the participants who voluntarily sign-up for a WHPP; and particularly those who want to stay in the programme but are prevented from participating in it regularly. Thus, the aim of this study was to identify and explore attendance barriers experienced by female Health Care Workers (HCWs) who voluntarily participated in a weekly one-hour multi-component training session, within a WHPP, over a one-year period. Methods This study was carried out within a RCT named FRIDOM (FRamed Intervention to Decrease Occupational Muscle pain) and was designed as a single-case study with an inductive approach for analysing the content of in-depth semi-structured qualitative interviews. Data was collected at two home care workplaces and two retirement homes in Denmark. Nine HCWs from the intervention group were selected as participants in the present study. Results The attendance barriers identified, consisted of three main themes and six related sub-themes: 1) organizational factors (work inflexibility, lack of support from team leaders), 2) intervention factors (training sessions organized outside normal work hours, incongruence between information received and reality, content and intensity of the program) and 3) individual factors (personal factors). Conclusion Organizational and intervention factors are the two most important attendance barriers in future WHPPs. To overcome these barriers; training sessions should be organized within or in connection with work hours, support should be secured from team management and work shifts should be planned to enable attendance for all participants. Furthermore, the attendance barriers may be minimized by including participants in the decision-making process. This relates to both the content and intensity of the intervention, not only in the planning stage but throughout the intervention process. Trial registration ClinicalTrials.gov. NCT02843269 - 06.27.2016 - retrospectively registered.